ALKBH5 demethylates the m 6 A modification of SOCS3 in microglia/macrophages and alleviates neuroinflammation after brain injury - Lin Cai; Yuqing Liang; Xiaoyu Li; Runxi Fu; Xingyu Niu; Yuxiao Jin; Yuxin Li; Yuheng Zhang; Pei Ouyang; Chen Wang; Qiuyuan Gong; Yang Yang; et al. (Proceedings of the National Academy of Sciences, 2025)
Microglia/macrophage-induced neuroinflammation plays a crucial role in the progression of traumatic brain injury (TBI). However, the involvement of N6-methyladenosine (m 6 A) RNA modifications in this process remains elusive. Single-cell RNA sequencing (scRNA-seq) and m 6 A RNA immunoprecipitation sequencing (MeRIP-seq) across multiple time points postinjury revealed a strong correlation between m 6 A modifications and genes enriched in microglia/macrophages. Furthermore, the m 6 A demethylase ALKBH5 was identified as a key regulator of dynamic m 6 A patterns at the injury site. ALKBH5 suppression in microglia/macrophages exacerbated neuroinflammation in vitro and worsened neurological deficits in controlled cortical impact (CCI) models. MeRIP-qPCR and RNA pull-down assays revealed SOCS3 was a downstream target of ALKBH5-mediated m 6 A demethylation. This demethylation stabilized Socs3 mRNA and enhanced its protein expression, which in turn suppressed neuroinflammation via inhibiting the JAK2-STAT3 pathway. Conversely, SOCS3 depletion impaired functional recovery after injury. These findings unveiled a critical ALKBH5–m 6 A–SOCS3 regulatory axis that mitigated microglia/macrophage-driven neuroinflammation after TBI, underscoring its potential as a therapeutic intervention target for TBI progression.